Effect of stocker receiving diet on subsequent pasture gains - F. Brazle; Gerry L. Kuhl; D. Harmon (Kansas Agricultural Experiment Station Research Reports, 1987)
Seven diets were fed for 27 days to newly arrived heifers to evaluate their impact on stocker gains during the receiving and pasture periods. The diets were as follows: soybean hulls plus soybean meal; suncured alfalfa plus wheat middlings; dehydrated alfalfa plus grain sorghum; distillers dried grain plus cottonseed hulls; brome hay plus 2 lb protein supplement/day; prairie hay plus 2 lb protein supplement/day; and a commercial receiving ration. During the receiving period, diets of soybean hulls plus soybean meal, distillers dried grain plus cottonseed hulls, and the commercial receiving ration produced the highest cattle gains. The soybean hull plus soybean meal diet and the commercial receiving ration resulted in the best combined dry lot and pasture gains as well.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Stocker cattle; Diet; Pasture gains